Counselor Communication to Optimize the Ability and Skills of Battalion 125/SMB Soldiers in the TNI AD KODAM I/BB Fighting Day Competition - Budianto H. Damanik (Budapest International Research and Critics University, 2022)
Observations of the battalion commander there were some athletes or soldiers who had very little mental self-confidence, this was due to the lack of athlete preparation in participating in training for the competition. Even though the soldiers had given their maximum effort in the race, it was still lacking. So that in order to create quality military members (athletes or soldiers), both physically, intellectually, and mentally who are perfect, each military unit has its own procedures for training them. The purpose of this study was to increase the self-confidence of soldiers in participating in training competitions on the Indonesian Army's fighting day. The method used in this study is a qualitative method with the type of phenomenology. The subjects used were members of the Infantry Battalion 125/SMB TNI AD Kodam I/BB totaling 13 people. Data was collected by means of in-depth interviews, participant observation and documentation. The data analysis is done by collecting, reducing, and displaying data and conclusion Drawing/verifying. The validity of the data was carried out covering credibility, transferability, dependability or reliability and confirmability tests. The results of this study indicate that the communication of the Battalion Commander as a counselor to the soldiers is very effective, the stages of communication carried out by the counselor are 4 of them; fact finding, planning, communicating, evaluation.